Myocarditis confirmed by biopsy presenting as acute myocardial infarction. Issue 1 (January 1985) - Costanzo-Nordin, M R; O'Connell, J B; Subramanian, R; Robinson, J A; Scanlon, P J
Abstract : Two cases of acute myocardial infarction occurred in association with myocarditis, which was confirmed by biopsy. The first patient suffered an anteroseptal and the second patient an inferior wall myocardial infarction shortly after an acute viral illness. In both patients, coronary angiography showed normal coronary arteries, and right ventricular endomyocardial biopsy confirmed myocarditis. Histological abnormalities attributable to ischaemic heart disease were absent. The first patient's condition became stable after immunosuppressive treatment. Myocarditis resolved spontaneously within three months in the second patient. Coronary artery spasm and myocardial involvement with a systemic disease were unlikely. Endomyocardial biopsy in patients with acute myocardial infarction and normal coronary arteries may be useful in identifying myocarditis associated with myocardial necrosis. Myocarditis in acute myocardial infarction in the absence of coronary artery obstruction has not previously been documented during life.